Serial Measurement of Superior Vena Cava Flow in Evaluation of the Clinical Severity of Pial Arteriovenous Fistula in an Infant - Ago, Mako; Masumoto, Kenichi; Uchiyama, Atsushi; Aihara, Yasuo; Okada, Yoshikazu; Kusuda, Satoshi (American Journal of Perinatology Reports, 2017)
Background Pial arteriovenous fistula (AVF) is composed of one or more direct arterial feeding vessels with a single draining vein without nidus. A patient with the disease with high-flow AV shunting in the neonatal period not only suffers from high-output cardiac failure but also shows secondary neurological sequelae. In vein of Galen aneurysmal malformation, superior vena cava (SVC) flow measurements provide useful prognostic information.Case Presentation We measured serial SVC flow in a male infant with pial AVF. The term infant presented with tachypnea, a heart murmur, and a cranial bruit after birth, and cranial magnetic resonance imaging and computed tomographic angiography revealed a pial AVF on the left sylvian fissure. SVC flow was at the upper normal limit at presentation. After 1 month, SVC flow gradually increased up to fourfold. Surgical resection of the pial AVF was performed and diagnosed as pial AVF on day 62. The SVC flow immediately decreased thereafter.Conclusion SVC flow reflects the shunt volume and may be a useful parameter for evaluating the optimal timing and effectiveness of intervention in pial AVF.
Keywords: pial arteriovenous fistula; superior vena cava flow; high-output cardiac failure; infant